2003
DOI: 10.1017/s1355617703970093
|View full text |Cite
|
Sign up to set email alerts
|

Syntactic language processing: ERP lesion data on the role of the basal ganglia

Abstract: The role of the basal ganglia in syntactic language processing was investigated with event-related brain potentials in fourteen neurologically impaired patients. Seven of these patients had basal ganglia lesions while 7 other patients primarily had lesions of the left temporo-parietal region excluding the basal ganglia. All patients listened to sentences that were either correct or included a verb argument structure violation. In previous experiments this type of violation elicited a biphasic pattern of an N40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
82
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(91 citation statements)
references
References 36 publications
6
82
0
3
Order By: Relevance
“…Furthermore, the use of an implicit manipulation task and the absence of both prime order and block order effects as well as the near absence of correlations between executive and rule parameters suggest that the striatum subserves rule application via language-specific operations. Yet, we do not preclude the possibility that the striatum, which is known to encompass functional circuits of executive functioning (e.g., Middleton & Strick, 2000), also controls lexical output at some post-linguistic level as implied by the data of Friederici et al (1999) and and Kotz et al (2003). This view is also coherent with findings showing that lexical operations such as word retrieval depend on controlled research strategies in the mental lexicon involving prefrontal and striatal structures (e.g., Rosen, Ojemann, Ollinger, & Petersen, 2000).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Furthermore, the use of an implicit manipulation task and the absence of both prime order and block order effects as well as the near absence of correlations between executive and rule parameters suggest that the striatum subserves rule application via language-specific operations. Yet, we do not preclude the possibility that the striatum, which is known to encompass functional circuits of executive functioning (e.g., Middleton & Strick, 2000), also controls lexical output at some post-linguistic level as implied by the data of Friederici et al (1999) and and Kotz et al (2003). This view is also coherent with findings showing that lexical operations such as word retrieval depend on controlled research strategies in the mental lexicon involving prefrontal and striatal structures (e.g., Rosen, Ojemann, Ollinger, & Petersen, 2000).…”
Section: Discussionsupporting
confidence: 75%
“…Similar sentence materials were also used with striatal damaged patients during ERP recollection (PD, vascular disorders). Several authors showed that the P600 component, which was hypothesised to index late stages of grammatical integration, is either absent (Friederici, Kotz, Werheid, Hein, & von Cramon, 2003;Kotz, Frisch, von Cramon, & Friederici, 2003) or reduced in these patients (Friederici, von Cramon, & Kotz, 1999). Such findings led to the assumption that the striatum subserves controlled post-linguistic processes allowing to verify and to integrate the output of early and automatic stages of syntactic processing .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is consistent with findings of delayed lexical-semantic activation during semantic priming in some patients with PD (Angwin et al, 2005;Arnott et al, 2001;Grossman et al, 2002). Also worthy of note, Kotz, Frisch, Von Cramon, and Friederici (2003) found that patients with a basal ganglia lesion demonstrated an Table 5. Mean amplitude of the N400 and P600 across electrode clusters for the first and second (repeat) presentation of stimuli Fig.…”
supporting
confidence: 89%
“…Studying language processing in PD allows researchers to analyze the effects of poorly functioning, yet still engaged corticostriato-cortical circuitry during language performance. Some of the studies reviewed in this chapter aimed at examining language processing in PD, to ultimately define the role of the basal ganglia in language processing (e.g., Ullman et al, 1997;Friederici et al, 2003;Grossman et al, 2003;Kotz et al, 2003). In the final section of this chapter, advice for communication guidelines that would guarantee a better quality of life for patients suffering from PD is given.…”
mentioning
confidence: 99%